2019
DOI: 10.1590/s2175-97902019000118194
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker responses (serum biochemistry) in pregnant female wistar rats and histopathology of their neonates exposed prenatally to pesticides

Abstract: Experiments were conducted to investigate the effects on health of pregnant female rats exposed to pesticides glyphosate and carbendazim. Glyphosate is used as herbicide and carbendazim as a fungicide; all are commercially available readily for various agricultural and domestic purposes. The hypothesis tested in this investigation is that pesticide exposure during pregnancy causes changes in biomarker responses like serum glucose level, total protein, total cholesterol, triglycerides, SGOT, SGPT, and billirubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It further may induce developmental and behavioral abnormalities, hematological malignancies, histopathological alterations, oxidative stress, genotoxicity and immunotoxicity as evidenced by animal modeling (Ubaidur Rahman et al, 2021). According to recent studies conducted by Upadhyay et al (2019), acephate exposure caused changes in biomarker responses like total protein and total cholesterol in female wistar rats. Liver and kidney collectively play an important role in metabolization process by transformation of thiono organophosphates accompanied by elimination process and act as main sites where maximum effects of pesticide by generation of oxidative stress can be seen.…”
Section: Resultsmentioning
confidence: 99%
“…It further may induce developmental and behavioral abnormalities, hematological malignancies, histopathological alterations, oxidative stress, genotoxicity and immunotoxicity as evidenced by animal modeling (Ubaidur Rahman et al, 2021). According to recent studies conducted by Upadhyay et al (2019), acephate exposure caused changes in biomarker responses like total protein and total cholesterol in female wistar rats. Liver and kidney collectively play an important role in metabolization process by transformation of thiono organophosphates accompanied by elimination process and act as main sites where maximum effects of pesticide by generation of oxidative stress can be seen.…”
Section: Resultsmentioning
confidence: 99%
“…However, the GLY supplied was in a mixture with seven other pesticides, and its specific effects were not studied. Upadhyay et al (2019) found higher levels of blood lipids (cholesterol and triglycerides) and transaminases, which are markers of liver damage, pregnant rats exposed to a GLY-based formula, and De Souza et al ( 2017) reported endocrine disrupting activity of GLY when observing lower levels of thyroid-stimulating hormone in rats after intervention with the GLY-based herbicide (Upadhyay et al 2019).…”
Section: Other Reproductive Effects Evaluated In Animal Modelsmentioning
confidence: 99%